2022
DOI: 10.5455/ovj.2022.v12.i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of heat-related illness in small animals presenting to veterinary practices in the UK between 2013-2018.

Abstract: Background: Heat-related illness (HRI) can affect all companion animals and is likely to become more common as global temperatures rise. The misconception that HRI is primarily a result of dogs being trapped in hot cars, highlights a lack of awareness of HRI risk factors within the UK companion animal population. Aim: This project aimed to review all species of small animal presentations of HRI to UK veterinary practices participating in the Small Animal Veterinary Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Previous studies have identified risk factors associated with developing HRI in dogs, including skull shape, bodyweight, age, breed and being overweight [ 24 , 25 , 26 ]. Whilst any dog can develop HRI if exposed to a high enough ambient temperature for long enough, brachycephalic dogs [ 24 , 25 , 27 ], overweight dogs [ 24 , 25 , 34 ], heavier dogs [ 24 ] and dogs aged 2–8 and over 12 years [ 24 ] have greater odds of developing HRI. However, our previous study [ 24 ] explored risk factors for the entire spectrum of severity of HRI presented for veterinary care and did not distinguish between differing risk factors across different severity grades of HRI [ 6 , 24 , 27 ], with only 14% of dogs developing severe disease [ 11 , 27 ] and a survival rate over 95% for dogs with mild/moderate disease [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have identified risk factors associated with developing HRI in dogs, including skull shape, bodyweight, age, breed and being overweight [ 24 , 25 , 26 ]. Whilst any dog can develop HRI if exposed to a high enough ambient temperature for long enough, brachycephalic dogs [ 24 , 25 , 27 ], overweight dogs [ 24 , 25 , 34 ], heavier dogs [ 24 ] and dogs aged 2–8 and over 12 years [ 24 ] have greater odds of developing HRI. However, our previous study [ 24 ] explored risk factors for the entire spectrum of severity of HRI presented for veterinary care and did not distinguish between differing risk factors across different severity grades of HRI [ 6 , 24 , 27 ], with only 14% of dogs developing severe disease [ 11 , 27 ] and a survival rate over 95% for dogs with mild/moderate disease [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst any dog can develop HRI if exposed to a high enough ambient temperature for long enough, brachycephalic dogs [ 24 , 25 , 27 ], overweight dogs [ 24 , 25 , 34 ], heavier dogs [ 24 ] and dogs aged 2–8 and over 12 years [ 24 ] have greater odds of developing HRI. However, our previous study [ 24 ] explored risk factors for the entire spectrum of severity of HRI presented for veterinary care and did not distinguish between differing risk factors across different severity grades of HRI [ 6 , 24 , 27 ], with only 14% of dogs developing severe disease [ 11 , 27 ] and a survival rate over 95% for dogs with mild/moderate disease [ 11 ]. This present study aimed to identify risk factors for HRI progression to severe or fatal disease within those dogs that were recorded with HRI; this information could facilitate more effective triage of affected dogs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important consequence of hyperthermia, described as an increase in body temperature above the accepted reference range [ 1 ] under conditions of elevated ambient temperature or exercise, is heat-related illness (HRI). The most important clinical signs of HRI are highly limiting for military working dogs (MWDs), as they include respiratory distress, lethargy, collapse, vomiting, diarrhea, hypersalivation, ataxia, seizures, hemorrhage, or coagulation problems, among others [ 2 ]. MWDs, in their different specialties, are confronted, together with their canine handlers, with extremely high temperature conditions, which can have a serious negative impact on the health of the dogs and the safety of the canine handlers.…”
Section: Introductionmentioning
confidence: 99%